Telling Lives in India - Jose Abraham (International Institute of Islamic Thought, 2006)
Telling Lives in India: Biography, Autobiography, and Life History is edited by David Arnold (professor of South Asian history) and Stuart Blackburn (research associate), both of the School of Oriental and African Studies (SOAS), London. The intellectual contributions of the editors and nine other distinguished scholars, all of whom belong to a range of academic disciplines, make this collection of eleven essays a remarkable and highly readable work on life histories – biographies, autobiographies, and oral accounts – from India. This volume grew out of the “Life Histories” project established at SOAS and out of various workshops held between 1998 and 2000 at SOAS, the London School of Economics, Oxford University, Cambridge University, and the British Library. In their well-thought-out and written “Introduction,” the editors explain why this volume was published. According to them, for a very long time the life history approach has been gaining wide acceptance among scholars belonging to various disciplines, such as women’s studies and black studies, due to a “growing distrust of ‘meta-narratives’” and a firm desire to “move towards a more nuanced, multi-stranded understanding of society and a greater recognition of the heterogeneity of human lives and lived ...